Selecting appropriate hardware For software radio systems - DOYLE, LINDA; NOLAN, KEITH EDWARD; O'MAHONY, DONAL EDWARD (My University, 2002)
Software radio is an emerging technology that offers great opportunities for the development of future wireless systems. Many different views exist on how to build both the software and hardware required by a software radio system. This paper focuses on the use of general-purpose processors for developing software radio hardware. A software radio testbed is used to demonstrate the advantages but also limitations of using a general-purpose processor. To overcome these limitations, a particular hardware approach is presented.
PUBLISHED
Keywords: Electronic & Electrical Engineering